2018
DOI: 10.1108/ijph-12-2016-0073
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of exercise referral as an intervention for Irish male prisoners presenting with mental health symptoms

Abstract: Purpose The use of exercise as an intervention to improve health in the general population is well documented. The purpose of this paper is to explore whether an exercise referral scheme can be an effective health promotion tool for male prisoners in Ireland, presenting with mental health symptoms. Design/methodology/approach This mixed methods study with a pre- and post-intervention design was conducted in Mountjoy Prison, Dublin, which has a capacity for approximately 790 prisoners. Reliable and validated sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 31 publications
0
26
0
2
Order By: Relevance
“…Exercise. Eight studies measured the effect of various forms of exercise on mental health outcomes [11][12][13][14][15][16][17][18]. While most studies examined exercise conducted in group settings, the interventions described all indicated that the activity would be possible to perform on one's own, without an activity facilitator, and all measured outcomes at the individual level were not likely to have been obtained as part of a group experience.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Exercise. Eight studies measured the effect of various forms of exercise on mental health outcomes [11][12][13][14][15][16][17][18]. While most studies examined exercise conducted in group settings, the interventions described all indicated that the activity would be possible to perform on one's own, without an activity facilitator, and all measured outcomes at the individual level were not likely to have been obtained as part of a group experience.…”
Section: Plos Onementioning
confidence: 99%
“…In one randomized trial, researchers measured state anxiety levels in 37 prisoners after the exercise group completed a six-week interval exercise training program [11]; another randomized trial measured depression, state anxiety, and trait anxiety in 60 prisoners after the exercise group underwent a 12-week exercise program [12]. In a nonrandomized trial, depression and anxiety were measured in 30 prisoners with pre-existing mental health symptoms after the exercise group completed a three-month exercise program [13]; another non-randomized trial measured somatization, anxiety, social dysfunction, and severe depression in 97 prisoners, where the individuals in the exercise group exercised at least three times each week [14]. A non-randomized trial measured distress levels of 173 prisoners, which were compared to those who engaged in exercise over four weeks [15].…”
Section: Plos Onementioning
confidence: 99%
“…Nevertheless, the majority of adolescents are undernourished and have an undiversified diet in low-and middle-income countries [11]. As an illustration, a monotonous cereal-based diet of adolescents is reported by former studies [12,13]. The majority of world adolescents (90%) live in low-and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of dietary diversity is a serious problem among the poor populations of developing countries, where diets are based predominantly on starchy staples which lack essential micronutrients and contribute to the burden of malnutrition and micronutrient deficiencies [12,13]. More specifically, women in the reproductive age group, adolescents, and children are most vulnerable to malnutrition due to low dietary intakes, inequitable distribution of food within the household, improper food storage and preparation, dietary taboos, infectious diseases, and health care [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, VR can play a prominent role in TR when talking about social interaction, since it shares the same virtual world between several stakeholders and thus creates a virtual social TR environment. Furthermore, virtual environments provide many interesting rehabilitation features that supersede the capabilities of a real-world rehabilitation setting (Keshner, 2004 ).…”
Section: Towards the Next Generation Of Tr Systemsmentioning
confidence: 99%